Clinical study to assess influence of immediate provisionalization and various implant morphologies on implant stability: A prospective clinical study - Qi, Meiyao; Deng, Shiyong; Tan, Zhen (Frontiers in Surgery, 2023)
As a heated topic nowadays, congenital craniofacial deformities affect patients both physically and psychologically. Implant-supported prostheses have been widely applied in clinical practice. Accordingly, initial stability of implants is essential for the long-term success of prosthesis therapy. To evaluate the influence of different implant morphologies and immediate provisionalization options on the change of implant stability, 94 patients were included and randomly grouped to receive implants therapy from three implant systems, meanwhile having the same opportunity of receiving immediate provisionalization or not. Implant stability quotient (ISQ) obtained from applying Resonance frequency analysis (RFA) of each implant were recorded each week. Marginal bone loss (MBL) of every implant was obtained from analysis of imaging examination as well. Parametric statistic was used for data analysis. Results showed that ISQ values of conical/straight/straight with micro-thread neck implants had no significant difference. Immediate provisionalization options could move the dip point of ISQ values ahead or delayed around one week, which were also relevant to implant systems. MBL values were proved to be unaffected by both two factors mentioned above.